Estymacja parametrów rozkładu na podstawie danych pogrupowanych za pomocą algorytmu EM : wyniki badań empirycznych - Huptas, Roman (Estimation of Parameters of Distribution from Grouped Data by Means of the EM Algorithm : Results of Empirical Researches, 2007)
In this article the Expectation-Maximization (EM) algorithm and its application are presented. The application is related to estimation of parameters of distribution in case data are grouped and may also be truncated. Results of a simulation experiment in which was used the Pearson chi-square goodness of fit test and results of empirical researches were presented. The EM algorithm as an iterative technique of estimation of parameters and classical methods of estimation were compared.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 358-366